Improvement of hardness in Ti-stabilized austenitic stainless steel - Sharifikolouei, Elham; Sarac, Baran; Micoulet, Alexandre; Magerl, Reinhard; Watari-Alvarez, Moyu; Hadjixenophontos, Efi; Burghard, Zaklina; Schmitz, Guido; Spatz, Joachim P. (Materials and design, 2022)
The high passivation capacity of austenitic stainless steel results in their excellent corrosion resistance. There are many ways to improve the hardness of austenitic stainless steel such as cold rolling or grain refinement. Herein, we explore the possibility of improving the hardness of AISI316-Ti stainless steel by generating an amorphous-nanocrystalline microstructure. ...
Gesehen am 09.11.2023